TOURISM, PROS AND CONS, AND ECO-TOURISM (Ustozlar uchun, 2026)
This article discusses the concept of tourism, its economic, cultural, and environmental impacts, as well as its advantages and disadvantages. Special attention is given to eco-tourism as a sustainable alternative to traditional mass tourism. The article highlights how tourism contributes to economic development and cultural exchange, while also addressing its negative effects such as environmental damage and cultural loss. Eco-tourism is presented as a responsible approach that balances development with environmental protection and community well-being.